Comparative analysis of 23-, 25-, and 27-gauge forceps stiffness and related displacement. Issue 3 (May 2021) - Pastore, Marco R; De Giacinto, Chiara; Cirigliano, Gabriella; Turco, Gianluca; Borelli, Massimo; Tognetto, Daniele
Purpose: To test the stiffness and displacement of different vitreous forceps. Physical features and deformation after multiple procedures were also measured. Methods: Eleven different 23-, 25-, and 27-gauge vitreous forceps were studied. The measurements were repeated loading the probe at different distances from the tip: at the top of the tip and 10 and 20 mm from the tip, respectively. For each probe, 10 successive identical bending tests were performed. The total length and the internal and external diameters of each forceps were also measured. Results: A total of 330 successive identical bending tests were performed. No progression in deformation after the repeated measurements was recorded ( p  > 0.05). In each gauge group, displacement differences were detected according to the manufacturing metal properties, the total length, and the thickness of the shaft wall. A minimal adequate model to describes forceps displacements in terms of their significant predictors, such as gauge, model, and load distance from the tip, was created. Conclusion: We provided a precise assessment of the stiffness and displacement of different vitreous forceps to enable surgeons to select the optimal instrument according to the benefits and limitations of each forceps.